Techno-Economic Evaluations on the Liquid Smoke Production from Coconut Shells (Case Study at CV Prima Rosandries, Jember) - Agus Dharmawan; Ida Bagus Suryaningrat; Siswoyo Soekarno; Fiqih Faresa Firdaus (Politeknik Negeri Lampung., 2020)
This research aimed to evaluate techno-economic on the liquid smoke production from coconut shells in small business, CV Prima Rosandries, Jember. The technical analysis was determined by calculating work capacity and yield, which resulted in 2.04 kg/hour dan 49.22%, respectively. In the cost analysis, CV Prima Rosandries required IDR 187,250,000 for its first cost and IDR 94,860,000 for its annual-operation costs, also gained the annual incomes IDR 151,200,000 and the estimated-asset value (salvage) IDR 15,525,000. In the investment evaluation, parameters, such as NPV, AE, BCR, RoR, and PBP, indicated that the business was in feasible and profitable condition. To gained the break-even point, CV Prima Rosandries obliged to sell 11,047 products and costly IDR 88,377,581. In the sensitivity analysis, percentage changes in the investment factors resulted in 22.77% for the interest rate, 82.72% for the first cost, 26.58% for the annual cost, and -16.67% for the annual benefit.